Myth and Identities in Romanticism – The Role of "Forerunner Identities" - Miftari, Vehbi (Journal of History Culture and Art Research, 2018)
Neither the romantic identity nor its spirit belongs to the romanticism itself. They aroused in earlier movements of cultural, religious, and political character. At the cultural level, the birth of romanticism was preceded by great intellectual movements: Humanism and Renaissance; at the social and political level, the powerful repercussions of the French and American revolution preceded the "awakening and growing of the idea of solidarity between individuals of one race, one language and one nation". At the ecclesiastical level, however, such were reformation and counter-reformation. These premises represent the forerunner identities of romanticism. They provoke its birth and determine its character. Only above them, romanticism revived the myth of common culture, paved the way for the formation of national languages, and institutionalized the awareness of the national state. This paper deals with this everlasting relationship between the romanticism and forerunner identities. The paper analyses the presence of the aesthetical premises in writing history in humanism and the transformation of this archetype in Romanticism. We also analyse the way how the Renaissance futures were transformed into a principle for history recognition and recreation of the myth in Romanticism. Closely, we will analyse the "identities" from which the romantic myth was born. The paper also discusses the idea how pre-existing ideologies of Humanism, Medieval Period, and how philobiblistic or pre-romantic authors influenced the creation of a romantic awareness and influenced the birth of the romantic myth.